Kebijakan Strategis Mitigasi Ancaman Peredaran Orbit Satelit terhadap Keamanan Nasional: Pendekatan Analytical Hierarchy Process - Herdiansyah, Herdis (Jurnal Keamanan Nasional, 2018)
The threat of circulating space orbit is considered by some to be a threat to the national security of one country because the potential dangers such as space junk produce significant damage to affected areas. But until now Indonesia, despite ratifying the UN convention on space, does not yet have a comprehensive mitigation strategy. This study aims to create policy scenarios for mitigating the threat of satellite orbit circulation so that it can be used as an alternative policy formulation for relevant institutions. The research method is carried out with a mixed method approach that is adjusted to each research objective such as using literature study and AHP analysis. AHP analysis shows that respondents want international cooperation to be built, both bilateral and multilateral cooperation must prioritize national security while upholding the values of friendship and mutual respect. Comprehensive space debris mitigation policies need to be formulated and defined as the basis for action. Considering that the impact of space debris is very dangerous and massive, the use of space technology is a necessity to be used to anticipate, deal with quickly, and minimize the impact of the disaster.